Niobium disulphide (NbS2)-based (heterogeneous) electrocatalysts for an efficient hydrogen evolution reaction. Issue 44 (1st November 2019) - Najafi, Leyla; Bellani, Sebastiano; Oropesa-Nuñez, Reinier; Martín-García, Beatriz; Prato, Mirko; Mazánek, Vlastimil; Debellis, Doriana; Lauciello, Simone; Brescia, Rosaria; Sofer, Zdeněk; Bonaccorso, Francesco
Abstract : The development of niobium disulphide (NbS2 )-based heterogeneous electrocatalysts for an efficient hydrogen evolution reaction. Abstract : The design of efficient and cost-effective catalysts for the hydrogen evolution reaction (HER) is the key for molecular hydrogen (H2 ) production from electrochemical water splitting. Transition metal dichalcogenides (MX2 ), most notably group-6 MX2 ( e.g., MoS2 and WS2 ), are appealing catalysts for the HER alternative to the best, but highly expensive, Pt-group elements. However, their HER activity is typically restricted to their edge sites rather than their basal plane. Furthermore, their semiconducting properties hinder an efficient electron transfer to the catalytic sites, which impedes a high rate of H2 production. Herein, we exploit liquid-phase exfoliation-produced metallic (1H, 2H and 3R) NbS2 nanoflakes, belonging to the class of metallic layered group-5 MX2, to overcome the abovementioned limitations. Both chemical treatment with hygroscopic Li salt and electrochemical in operando self-nanostructuring are exploited to improve the NbS2 nanoflake HER activity. The combination of NbS2 with other MX2, in our case MoSe2, also provides heterogeneous catalysts accelerating the HER kinetics of the individual counterparts. The designed NbS2 -based catalysts exhibit an overpotential at a cathodic current of 10 mA cm −2 ( η 10 ) as low as 0.10 and 0.22 V vs. RHE in 0.5 M H2 SO4 and 1 M KOH, respectively. In 0.5 M H2 SO4, the HER activity of the NbS2 -based catalysts is also superior to those of the Pt/C benchmark at current densities higher than 80 mA cm −2 . Our work provides general guidelines for a scalable and cost-effective exploitation of NbS2, as well as the entire MX2 portfolio, for attaining a viable H2 production through electrochemical routes.